2020
DOI: 10.4187/respcare.07605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prognostic Factors Between Direct and Indirect Pediatric ARDS

Abstract: BACKGROUND: Pediatric ARDS is a heterogeneous disease entity with high morbidity and mortality. In this study, we categorized pediatric ARDS by direct and indirect initial triggering events and identified characteristics of survivors and nonsurvivors in these 2 subtypes. METHODS: This was a single-center, retrospective, observational study that included critically ill subjects with pediatric ARDS (age 1 month to 18 y) who had undergone mechanical ventilation support and had been admitted to our 14-bed, multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Our prospective study reported the overall incidence of PARDS accounted for 10.7% of the screened population. The incidence of sepsis-related PARDS was 19.7%, which was comparable to other studies that reported rates ranging from 8.2% to 22%, [ 5 19 20 ]and PICU mortality rate was 30.7% (8/26) which was higher than a recent retrospective study that revealed the PICU mortality rate of sepsis-related PARDS was 24.6%. [ 21 ]A single-center retrospective study involving 203 sepsis-related PARDS from 828 sepsis patients showed that ARDS severity, PRISM III, and the number of organ dysfunction were associated with increased 90-day mortality in sepsis-related PARDS.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our prospective study reported the overall incidence of PARDS accounted for 10.7% of the screened population. The incidence of sepsis-related PARDS was 19.7%, which was comparable to other studies that reported rates ranging from 8.2% to 22%, [ 5 19 20 ]and PICU mortality rate was 30.7% (8/26) which was higher than a recent retrospective study that revealed the PICU mortality rate of sepsis-related PARDS was 24.6%. [ 21 ]A single-center retrospective study involving 203 sepsis-related PARDS from 828 sepsis patients showed that ARDS severity, PRISM III, and the number of organ dysfunction were associated with increased 90-day mortality in sepsis-related PARDS.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study found the worse ventilator parameter, and oxygen index, including PF ratio, was associated with higher mortality in the direct risk factor group, while lactate and pSOFA scores were associated with higher mortality in the indirect risk factor group. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%